Corporate Social Responsibility Practices in the Lebanese Casual Dining Industry: An Exploratory Study of Rural Versus Urban Settings - Mira THOUMY; Jennifer ABOU HAMAD; Omar SAKR; Christelle KHALIFE (Communications of International Proceedings, 2021)
This paper examines the different ISO26000 core subjects practices in the casual dining industry. It explores the human rights practices, the labour practices, the environmental practices, the fair operating practices, the consumer issues and the community involvement practices. Based on the case studies, it was found that the companies were performing some aspects of CSR without their knowledge and without official classification, and that the practices were implemented in fragmented ways rather than a part of a business strategy.
Keywords: Corporate social responsibility (CSR); CSR Practices; ISO26000; Casual Dining